PRODUCTION OF ALKALINE PROTEASE WITH IMMOBILIZED CELLS OF BACILLUS CEREUS STRAIN S8 IN VARIOUS MATRICES - LAKSHMI B.K.M,; HEMALATHA K. P. J, (International Journal of Pharma and Bio Sciences, 2015)
The purpose of this investigation was to study the effect of Bacillus cereus strain S8 cells immobilized in various matrices, such as calcium alginate, k-Carrageenan, polyacrylamide, agar-agar, and gelatin, for the production of alkaline protease. Calcium alginate was found to be an effective and suitable matrix for higher alkaline protease productivity compared to the other matrices studied. All the matrices were selected for repeated batch fermentation. The average specific volumetric productivity with calcium alginate was 210 ± 0.15 U/ml, which was 57% higher production over the conventional free-cell fermentation. The protease yield and operational stability of the immobilized system were increased by tailoring the capsules’ characteristics. Capsules prepared from 3% (w/v) sodium alginate and 2.0% (w/v) CaCl2 were the best support for cell immobilization, providing 7.9 fold higher protease productions in comparison to the freely suspended cells. Immobilized biocatalysts sustained 94% of their initial productivity over five sequential batches in a 10-day period, while protease production by free cells declined sharply after further use.